2005
DOI: 10.1016/j.molcel.2004.11.049
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of p21WAF1/CIP1 Stability by WISp39, a Hsp90 Binding TPR Protein

Abstract: p21(WAF1/CIP1), a cyclin-dependent kinase inhibitor and a critical regulator of cell cycle, is controlled transcriptionally by p53-dependent and -independent mechanisms and posttranslationally by the proteasome. We have identified WISp39, a tetratricopeptide repeat (TPR) protein that binds p21. WISp39 stabilizes newly synthesized p21 protein by preventing its proteasomal degradation. WISp39, p21, and hsp90 form a trimeric complex in vivo. The interaction of WISp39 with Hsp90 is abolished by point mutations wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(127 citation statements)
references
References 33 publications
5
121
0
1
Order By: Relevance
“…However, it was recently reported that p21 can be negatively regulated by MDM2 independently of any effects on p53 (Zhang Z et al, 2004b). It is therefore possible that the GA-induced p21 accumulation observed in the present study could have resulted from loss of this repressive effect, although another recent report suggests that Hsp90 plays a direct role in regulating p21 protein stability (Jascur et al, 2005).…”
Section: Discussionmentioning
confidence: 48%
“…However, it was recently reported that p21 can be negatively regulated by MDM2 independently of any effects on p53 (Zhang Z et al, 2004b). It is therefore possible that the GA-induced p21 accumulation observed in the present study could have resulted from loss of this repressive effect, although another recent report suggests that Hsp90 plays a direct role in regulating p21 protein stability (Jascur et al, 2005).…”
Section: Discussionmentioning
confidence: 48%
“…It remains to be seen whether cy1 binds one or more factors that promote Cdk2-independent degradation of p21. In addition, Wisp39 was recently identified as a factor that binds the p21 N terminus and stabilizes the p21 protein (42). It is unclear whether Cdk2 activity may influence the stabilization of p21 by Wisp39.…”
Section: Discussionmentioning
confidence: 99%
“…These include a WISp39-associated chaperone pathway, 23 an SCF skp2 -dependent pathway [24][25][26] and an hdm2-dependent pathway. 27,28 Overwhelming cellular, biochemical and genetic evidence a transcriptional blockade prevented p53-induced-accumulation of p21 but not other p53 targets in S-phase RKO cells.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%